LA COMUNICACIÓN DISRUPTIVA EN LA PUBLICIDAD DE PEQUEÑOS Y MEDIANOS NEGOCIOS DEL CANTÓN LA MANÁ. - Pusay Pastuña, Paola Patricia (2022)
The present research project was carried out with the purpose of presenting a study of disruptive communication and its influence on the advertising of small and medium-sized businesses in the La Maná Canton, with the objective that it has a boost in the growth of its sales. thinking of the owners of the businesses to which it is directed. Through the research methodology, a survey was carried out among microentrepreneurs in the La Maná canton, in order to obtain relevant information about the degree of knowledge on the subject of disruptive communication in the advertising of their enterprises. With the data collected through a questionnaire of questions, it was determined that it is possible to develop a strategy for the dissemination of advertising in the businesses of the La Maná canton with the aim of improving their sales. Upon reaching the proposed objective, there will be an improvement in the advertising field, thus guaranteeing effective, fast and efficient marketing to achieve the sales proposed by the small and medium-sized businesses of the La Maná canton.